Peningkatan Keterampilan Kerja Pemuda melalui Pelatihan SDM berbasis Kompetensi di Yayasan Tajaul Karomah Desa Situ Gadung Kabupaten Tangerang - Widowati, Widowati; Astutik, Endang Puji; Karlina, Dira (Jurnal PKM Manajemen Bisnis, 2025)
The increasing demand for skilled labor in the workforce highlights the urgent need to equip youth with relevant competencies. In response, a community service program titled "Enhancing Youth Employability through Competency-Based Human Resource Training at Tajaul Karomah Foundation, Situ Gadung Village, Tangerang Regency" was conducted to improve the employability of local youth. The program aimed to develop participants' work-related skills through structured, competency-based training. The activity took place on May 4, 2025, at the Tajaul Karomah Foundation and was implemented by 15 lecturers from Pamulang University. A total of 45 participants joined the program, including local youth, community members, teachers, and students from Situ Gadung Village. The training was delivered through a combination of lectures, hands-on practice, group discussions, and Q&A sessions. Topics included soft skills, professional communication, and basic job readiness. The results showed a significant improvement in participants’ understanding of workplace demands and their confidence in applying newly acquired skills. Participants expressed enthusiasm and requested further training opportunities. This community service initiative successfully contributed to the development of human resources at the village level, fostering greater readiness among youth to enter the labor market.